Opportunities And Challenges Of Multicultural Education In School Learning - Haris Firmansyah (Jurnal Scientia, 2024)
This study aims to analyze the opportunities and challenges in implementing multicultural education in Indonesia. The literature review research method was used to understand students' perspectives on cultural diversity, tolerance, and cross-cultural communication skills and to identify resistance, stereotypes, prejudice, and resource constraints in the implementation of multicultural education. The results show that multicultural education provides opportunities to enrich students' learning experiences by introducing them to various cultural perspectives and values. However, challenges such as resistance to cultural diversity, lack of understanding of the importance of multicultural education, and limited resources and support are still barriers to its implementation. Overcoming these challenges requires strategies such as raising awareness and understanding, developing appropriate learning materials, and collaboration between educational institutions, governments, and communities. By implementing these strategies holistically, schools can create an inclusive and meaningful learning environment for all students.